2k-3(2k-3)=45

Simple and best practice solution for 2k-3(2k-3)=45 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2k-3(2k-3)=45 equation:


Simplifying
2k + -3(2k + -3) = 45

Reorder the terms:
2k + -3(-3 + 2k) = 45
2k + (-3 * -3 + 2k * -3) = 45
2k + (9 + -6k) = 45

Reorder the terms:
9 + 2k + -6k = 45

Combine like terms: 2k + -6k = -4k
9 + -4k = 45

Solving
9 + -4k = 45

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + -4k = 45 + -9

Combine like terms: 9 + -9 = 0
0 + -4k = 45 + -9
-4k = 45 + -9

Combine like terms: 45 + -9 = 36
-4k = 36

Divide each side by '-4'.
k = -9

Simplifying
k = -9

See similar equations:

| 5=7w+8w+2 | | 60=-12r | | -9(b-4)-1= | | X=842-13 | | k/17=-7/17 | | (3x+14)/5=8-2x | | 4x+2+3x-8=8 | | a-19=-25 | | 2x-y+150=180 | | z+4=12 | | 1(2/3)+(9/5) | | X+199=99 | | 45/0.15 | | 10/400 | | 10/40 | | -3[4-(3b+3)]=4-3(3b+5) | | (x/7)=(12/4) | | 3r^2-7r=3 | | 2r+5s=39 | | 5r-2s=25 | | -3a+b=20 | | 3(y+1)-9x=-12 | | 3a+7b=-4 | | -70=11-9m | | -10x-28y=26 | | 5x+14y=-13 | | 3x+2x^2-x= | | t/7-7/t=0 | | (2/3)x+(2/7)=2+(20/21) | | (2/3)x+(2/7)=2(20/21) | | -3[4-(3b+3)]4-3=(3b+5) | | 8-(9-6x)=2x-6 |

Equations solver categories